Human Resource Management Strategy and Safety Culture as Competitive Advantages in Order to Improve Construction Company Performance - Winda widyanty; Apollo Daito; Setyo Riyanto; Dewi Nusraningrum (Universitas Trisakti, 2020)
This study was conducted to analyze human resource management strategies and safety culture as competitive advantages to improve company performance in the construction industry in Indonesia and to identify related factors to achieve competitive advantage in the construction industry. Primary data were collected by distributing questionnaires to 174 construction companies in Indonesia. The results of SEM data processing using the Lisrel software show that recruitment, selection, performance management, compensation, and training and development that are integrated with safety culture can be a competitive advantage and can improve the performance of construction companies in Indonesia. Future studies can use this strategic human resource management model in different industrial sectors by increasing the number of samples so that the research results can be generalized to the intended population.